2020
DOI: 10.3389/fendo.2020.577537
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Algorithms for the Prediction of Central Lymph Node Metastasis in Patients With Papillary Thyroid Cancer

Abstract: Background: Central lymph node metastasis (CLNM) occurs frequently in patients with papillary thyroid cancer (PTC), but performing prophylactic central lymph node dissection is still controversial. There are no reliable models for predicting CLNM. This study aimed to develop predictive models for CLNM by machine learning (ML) algorithms. Methods: Patients with PTC who underwent initial thyroid resection at our hospital between January 2018 and December 2019 were enrolled. A total of 22 variables, including cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 39 publications
1
51
0
Order By: Relevance
“…All results have been confirmed in ML algorithms. Our study suggests that males are frequently found to be more susceptible to CLNM, which is supported by findings of previous studies ( 12 , 29 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…All results have been confirmed in ML algorithms. Our study suggests that males are frequently found to be more susceptible to CLNM, which is supported by findings of previous studies ( 12 , 29 ).…”
Section: Discussionsupporting
confidence: 93%
“…Compared with studies attempting to predict the risk of central compartment lymph node metastases in PTC ( 12 , 27 , 28 , 33 , 34 ), our work has several strengths. First, few studies have ever focused on the subgroup of patients who suffer from clinically low-risk PTC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Algorithmic decision support tools, computer-assisted navigation and surgical robots have served in the clinic (3,4). Machine learning (ML) has been widely used in healthcare data analysis and some in spinal surgery (5,6). By the comparison among ML algorithms, a better predictive model can be constructed to predict cement leakage after percutaneous vertebroplasty.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al ( 29 ) studied one or a combination of machine learning methods in Logistic regression, Random forest, XGBoost, and GBDT to construct lymph node metastasis in patients with poorly differentiated intramucosal gastric cancer. Supervised machine learning methods including random forest classifier, artificial neural network, decision tree, gradient boosting decision tree, extreme gradient boosting, and adaptive boosting can also be used to predict central lymph node metastasis in patients with papillary thyroid cancer ( 30 ). Besides improving the accuracy of overall prediction, we further focus on boosting the performance on sensitivity by the designed “Two-Stage Cost Sensitive Hypergraph Learning.” One stage is to capture the cost sensitivity of negative cases in the latent feature spaces, which will enable the hypergraph model to allocate the lymph node involvement cases more weights.…”
Section: Introductionmentioning
confidence: 99%